PENENTUAN AKTIVITAS ANTIOKSIDAN DARI DAUN BUAS-BUAS (Premna serratifolia L.) MENGGUNAKAN METODE DPPH (2,2-diphenyl-1-picrylhydrazyl) - Isnindar Isnindar; Subagus Wahyuono; Sitarina Widyarini; Yuswanto Yuswanto (Majalah Obat Tradisional, 2016)
Antioxidant is a substance that in small concentrations can significantly inhibit or prevent oxidation on the substrate. Buas-buas (Premna serratifolia L.) is one of the plants that have antioxidant effect. The antioxidant activities of the wasbenzen and ethanol extracts of buas-buas leaves were determined by DPPH method using spectrophotometer UV-Vis. Data resulted from the analysis of antioxidant activity (IC50) is 532.24 μg/mL of wasbenzen extract, 24.40 μg/mL of ethanol extract, and 1.83 μg/mL of vitamin C.